To the Influence of Material Dispersion on the Intermodal Interference in Optical Fibres - Ivan Turek; Daniel Kacik; Ivan Martincek (Communications - Scientific letters of the University of Zilina, 2003)
The comparison of computed and measured spectral dependence of intermodal interference in step-index optical fibre presented in this paper shows the influence of material dispersion on the intermodal interference in optical fibres. It is shown that the influence of material dispersion on intermodal interference is high enough to allow determination of the material dispersion difference of core and cladding of optical fibres.